SPACES OF MEMORY AND URBAN PRACTICES: AUTHORITY NARRATIVE AND ARCHITECTURE IN THE EXPERIENCE OF VILANOVA ARTIGAS DURING THE BRAZILIAN CIVIL-MILITARY DICTATORSHIP - AGAPITO, VICTOR HUGO DE SANTANA (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2022)
Aiming at a multidisciplinary understanding of the Brazilian authoritarian experience between the 1960s and 1980s, discusses the phenomenon through its narrative and spatial elements, based on the experience and work of architect João Batista Vilanova Artigas (1915-1985). To do so, initially, it explores the relationships between space, sensory experience and the use of legal narrative for its transformation and the materialization of policies of exception, so that; Based on the experience and work of Vilanova Artigas, it is possible to analyze how architectural practice is used as a form of resistance and confrontation with the power exercised by Law in authoritarian regimes to; finally, to verify the historicity of the experience lived by the architect from Curitiba in a multifaceted perspective – in Law and in Architecture – and its consector contributions to the democratic debate in the present time. It is, therefore, an exploratory research, carried out mainly through a literature review and document consultation, whose data collected are the object of qualitative analysis.